Translated Al-Quran retrieval system employing Bigram using Apache / Norsharizan Muhamad - Muhamad, Norsharizan (2004)
Information retrieval is one of the fields in information technology. The main function of information retrieval is to provide the tools to perform searching effectively and efficiency. This project is to broad the study on information retrieval based on Malay query words and databases. This project is the enhancement of current project which had used thesaura. ft is build to help users who are interested to know about certain subject matters from the Al-Quran, where the document retrieval system will automatically retrieve all relevant documents in response to the user queries. This project will employ bigram algorithm that will be used to retrieve translated Al-Quran documents using Malay keywords. Then evaluate the efficiency and effectiveness of the bigram method by comparing it. with other conflation method that had been carried out by previous student in retrieving translated Ai-Quran documents. This project will run on Apache and will be implement on-line so that it can be installed by users on personal computer. Apache provides many features that make it a very powerful local Web server.